Effect of Good Corporate Governance on Mining Firm Financial Performance: Company Size Moderation, Indonesia 2021–2024 - Siti Nurmala Lubis; Azhar Maksum; Keulana Erwin (International Forum of Researchers and Lecturers, 2026)
A company's financial performance is a key indicator in assessing management's success in managing company resources and creating shareholder value. This study aims to analyze the influence of Good Corporate Governance mechanisms, as proxied by the size of the board of commissioners, the board of directors, the audit committee, and institutional ownership, on company financial performance, and to examine the role of company size as a moderating variable. The population in this study was mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. Based on purposive sampling criteria, a sample of 36 companies was obtained, with a total of 112 observations. The data used were secondary data, and the analytical method employed was panel data regression with a fixed effects model and moderation analysis. The results showed that the size of the board of commissioners had a positive and significant effect on financial performance, while the size of the board of directors, the audit committee, and institutional ownership did not significantly influence financial performance. Furthermore, company size did not moderate the effect of the size of the board of commissioners, the board of directors, the audit committee, and institutional ownership on financial performance.